2022
DOI: 10.1101/2022.02.04.479122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Alcohol Consumption Alters Home-Cage Behaviors and Responses to Ethologically Relevant Predator Tasks in Mice

Abstract: Alcohol use disorders (AUD) are the most prevalent substance use disorders worldwide. Considering recent reports indicating an increase in alcohol use particularly in females, it is vital to understand how alcohol history impacts behavior. Animal model research on withdrawal-associated affective states tends to focus on males, forced alcohol paradigms, and a few traditional anxiety/stress tests. While this has been essential, heavy alcohol use triggers adverse withdrawal-related affective states that can influ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…Post hoc Šidák corrected multiple comparisons test did not reveal any significant differences (30pA: p = 0.065 and 40pA: p = .108). We only found differences between alcohol and water exposed males in the input resistance ( We had previously shown (Neira et al, 2022) that female mice in 6-8hr acute withdrawal had increased escape behaviors in the looming disc test, therefore, we hypothesized that inhibiting PVN CRH neurons will restore female behavior in this test. First, we established that increased escape responses compared to mCherry water controls in 6day alcohol withdrawal mCherry mice were also seen in the looming disc test (Fig 5A In fact, Chi-square analysis between mCherry water and alcohol mice during Escape, Freeze, or neither escape/freeze behavioral responses to loom revealed significant differences in behavior (Fig 5B X 2 (1, N =130) = 11.3502, p =.003), with alcohol mCherry mice displaying greater escape responses.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Post hoc Šidák corrected multiple comparisons test did not reveal any significant differences (30pA: p = 0.065 and 40pA: p = .108). We only found differences between alcohol and water exposed males in the input resistance ( We had previously shown (Neira et al, 2022) that female mice in 6-8hr acute withdrawal had increased escape behaviors in the looming disc test, therefore, we hypothesized that inhibiting PVN CRH neurons will restore female behavior in this test. First, we established that increased escape responses compared to mCherry water controls in 6day alcohol withdrawal mCherry mice were also seen in the looming disc test (Fig 5A In fact, Chi-square analysis between mCherry water and alcohol mice during Escape, Freeze, or neither escape/freeze behavioral responses to loom revealed significant differences in behavior (Fig 5B X 2 (1, N =130) = 11.3502, p =.003), with alcohol mCherry mice displaying greater escape responses.…”
Section: Resultsmentioning
confidence: 88%
“…After habituation, the home-cage with only the bedding and mouse was placed in a ~60 lux low-light sound attenuated chamber that contained an overhead camera for filming behavior. Rearing, digging, grooming, and locomotion were analyzed for a 15minute period using DeepLabCut and SimBA mediated automatic analysis as previously discussed (Neira et al, 2022).…”
Section: Home-cage Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of machine learning and deep learning enables the simultaneous specialization and standardization of behavior classification processes across neuroscience research. Previous studies have utilized various deep learning techniques to look at behaviors that correlate with pain states (Bohic et al, 2021 ), social behavior in stressed mice (Rodriguez et al, 2020 ; Lee et al, 2022 ), depressive behavior in stressed mice (Rivet-Noor et al, 2022 ), and reward behavior in mice models of food seeking (Zhang et al, 2022 ) or drug and alcohol abuse (Campos-Ordoñez et al, 2022 ; Neira et al, 2022 ). This allows behavioral neuroscientists to explore behavioral nuances in a more generalizable way (Goodwin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that various aspects of EtOH withdrawal (including increased anxiety-like behavior, seizures, and EtOH intake during withdrawal) increase with repeated EtOH withdrawal cycles (Becker, 1996; Holter et al, 1998; Lopez and Becker, 2005; Overstreet et al, 2004; Rimondini et al, 2003; Zhang et al, 2007). Another possibility is that the environment was too anxiogenic, creating a ceiling effect of anxiety-as suggested by a recent study of testing outside the homecage(Neira et al, 2022). Future studies will investigate negative affect as it occurs in the home cage, as it may be more indicative of withdrawal behaviors.…”
Section: Discussionmentioning
confidence: 99%